1968
DOI: 10.3109/00365596809135362
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Enzyme Studies Following Renal Ischaemia in Dogs

Abstract: In recent years the analysis of urinary enzymes has attracted interest as a possible aid to the diagnosis of renal disease. We have produced renal ischaemia of varying duration in dogs and then studied the activity of different enzymes in the urine. In spite of the fact that the damage to the kidney was so small as to produce only a slight or moderate effect on creatinine clearance and inulin and PAH extraction, we observed in the lirst few hours following ischaemia a very marked increase in the outflow of leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Urinary levels of lysozyme (mucopeptide N-acetyl-muramyl hydrolase, EC 3.2.1.17) and various acid hydrolases in patients with urinary levels of these enzymes appear to have limited value in diagnostic procedures (3,4,14,20). Lysozyme levels of urine are elevated in animals by a number of experimental procedures, including renal ischemia in dogs (7), ingestion of mercuric chloride (14), renal homograph rejection in dogs (10), classical runt disease in mice (17), and the injection (intraperitoneal) of egg white lysozyme in rats (9,13). Recently, the intrarenal distribution of lysozyme in normal rat kidneys (12,16) and induced changes in the concentrations of renal lysozyme (6,9,12,15) have been reported.…”
mentioning
confidence: 99%
“…Urinary levels of lysozyme (mucopeptide N-acetyl-muramyl hydrolase, EC 3.2.1.17) and various acid hydrolases in patients with urinary levels of these enzymes appear to have limited value in diagnostic procedures (3,4,14,20). Lysozyme levels of urine are elevated in animals by a number of experimental procedures, including renal ischemia in dogs (7), ingestion of mercuric chloride (14), renal homograph rejection in dogs (10), classical runt disease in mice (17), and the injection (intraperitoneal) of egg white lysozyme in rats (9,13). Recently, the intrarenal distribution of lysozyme in normal rat kidneys (12,16) and induced changes in the concentrations of renal lysozyme (6,9,12,15) have been reported.…”
mentioning
confidence: 99%
“…There is a vast increase in levels of acid phosphatase and fl-glueuronidase in the blood of the renal vein, a result that is not found in any other group studied. The liberation of lysosomal enzymes under the influence of isehaemia has previously been demonstrated in the intestine [3,35], but does not appear to have been studied in the renal vein blood after renal ischaemia: Other workers have studied various non-lysosomal enzymes, and have concluded that their increase in the renal vein was due to cellular destruction [14,19,20].…”
Section: Renal Ischaemiamentioning
confidence: 99%
“…Urinary levels of lysozyme (mucopeptide N-acetyl-muramyl hydrolase, EC 3.2.1.17) and various acid hydrolases in patients with urinary levels of these enzymes appear to have limited value in diagnostic procedures (3,4,14,20). Lysozyme levels of urine are elevated in animals by a number of experimental procedures, including renal ischemia in dogs (7), ingestion of mercuric chloride (14), renal homograph rejection in dogs (10), classical runt disease in mice (17), and the injection (intraperitoneal) of egg white lysozyme in rats (9,13). Recently, the intrarenal distribution of lysozyme in normal rat kidneys (12,16) and induced changes in the concentrations of renal lysozyme (6,9,12,15) have been reported.…”
mentioning
confidence: 99%